Case Study of Intervention using Mint Leaf Aroma Therapy in Bronchial Asthma Patients - Dadi Hamdani; Elis Roslianti; Ade Fitriani; Dhani Andriansyah (LPPM STIKes Muhammadiyah Ciamis, 2022)
Objective: This case study was conducted to present interventions and to see the effectiveness of using mint leaf aromatherapy interventions in improving ineffective breathing problems in clients with bronchial asthma. Method: The research design used was a descriptive method with a case study approach, which included an intensive study of one unit of asthma cases with ineffective breathing patterns. Enforcement of nursing diagnoses refers to the Indonesian Nursing Diagnosis Standards (IDHS). Indonesian Nursing Intervention Standards (SIKI) and Indonesian Nursing Outcomes Standards (SLKI) The focus of the intervention in this case study was giving mint leaf aromatherapy, which was carried out for 3 days in the emergency room at the Banjar City Public Hospital. Nursing evaluations are documented using the SOAPIER method. Result: Based on the results of the study conducted on Mr. S on May 28, 2023, it was found that Mr. S was 48 years old with a medical diagnosis of bronchial asthma with a nursing problem, namely an ineffective breathing pattern associated with difficulty breathing (D.0005). After the act of giving aromatherapy for 3 days to the patient, which aims to reduce shortness of breath by widening the airways and thinning the phlegm, The results obtained in the Tn.S. patient said that it was better than before; there was no coughing up phlegm, no wheezing breath sounds, BP: 140/110 MmHg, pulse: 90x/minute, temperature: 36.5°C, RR: 23x/minute, and SpO: 99%. Conclusion: The mint leaf aromatherapy intervention has proven to be useful for increasing respiration and spo within normal limits, The benefits of this therapy will be maximized if it is carried out periodically and gradually